Reverse inequalities for geometric and power means - Korenovskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We establish exact bounds for the positive and negative exponents of summability of the power mean of a function in the case where this mean satisfies the reverse Jensen inequality.